Rancang Bangun Sistem Administrasi Keuangan Masjid Ar-Rahman Berbasis Web - ardhani, Muhammad Ridwan Ardhani; Maryam (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2024)
Masjid Ar-Rahman currently still manages its finances manually, and it is very limited. The manual recording system is considered ineffective, and the congregation cannot have detailed knowledge about the financial reports. Therefore, an information system is needed to record and manage the funds coming in and out of the mosque in real time. The objective of this research is to design a system used for creating a mosque financial administration system based on a website. The financial administration system is designed using the waterfall method, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system is developed using the Code Igniter (CI) programming language, PHP, and MySql as the database to store data inputted through the application. The author conducts testing using the black box testing method, which tests from the functionality aspect. With the existence of this system, it is expected to assist in the management of charity funds, incoming and outgoing cash, and reduce errors in financial calculations, thus enabling ease in the preparation of detailed, accurate, and periodic financial reports. Testing on this system is carried out using the black box and system usability scale (SUS) methods. The result of the black box testing is that the system runs well and as expected. The result obtained from the SUS testing on the financial administration system of Masjid Ar-Rahman is 72.1. This result indicates that the system is on an acceptable scale, and it can be said that this system is suitable for use.